Obituaries, newspaper cuttings, typescript speeches and commemorations relating to deceased members of the I.R.A. (McC - M) - O'Donoghue, Florence, 1895-1967 (1956)
Material relates to Patrick McCarthy (20 Nov. 1920), Patrick McCartan (Mar. 1963), Donnchadh Mac Neillis (Dec. 1954), Sean Moylan (Nov. 1965), Joe Murphy (1920), Tadg Murphy, (c.1960) and Walter Leo Murphy (June 1921). Includes a photograph of the burial of Tadg Murphy.
Keywords: Irish Republican Army; Ireland -- History -- 1922-